2021
DOI: 10.3390/rs13234767
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Effects of Temperate Forests in Regulating Regional Temperature and Precipitation Pattern across Northeast China

Abstract: The temperate forests in Northeast China are an important ecological barrier. However, the way in which temperate forests regulate the regional temperature and water cycling remains unclear. In this study, we quantitatively evaluated the role that temperate forests play in the regulation of the regional temperature and precipitation by combining remote sensing observations with a state-of-the-art regional climate model. Our results indicated that the forest ecosystem could slightly warm the annual air temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…The research area of this study is the Northeast China (NEC), which includes the Heilongjiang, Jilin, and Liaoning provinces, is located from 118 • 50 E to 135 • 09 E and 38 • 42 N to 53 • 35 N (Figure 1) [42]. NEC has the considerable climatic and topographical gradients, and the main topography of NEC is mountains and plains, with mountains in the east, west and north, and plains in the middle and south [43]. Due to geographical location NEC belongs to a temperate continental monsoon climate [44], which is divided into a warm temperate zone, temperate zone, and cold temperate zone from south to north and has obvious differences in humidity from east to west [45].…”
Section: Study Areamentioning
confidence: 99%
“…The research area of this study is the Northeast China (NEC), which includes the Heilongjiang, Jilin, and Liaoning provinces, is located from 118 • 50 E to 135 • 09 E and 38 • 42 N to 53 • 35 N (Figure 1) [42]. NEC has the considerable climatic and topographical gradients, and the main topography of NEC is mountains and plains, with mountains in the east, west and north, and plains in the middle and south [43]. Due to geographical location NEC belongs to a temperate continental monsoon climate [44], which is divided into a warm temperate zone, temperate zone, and cold temperate zone from south to north and has obvious differences in humidity from east to west [45].…”
Section: Study Areamentioning
confidence: 99%
“…This implies that the impact of vegetation on precipitation is greater than the response of vegetation to precipitation changes. The results of previous studies have confirmed that temperate forests in Northeast China have the ability to regulate the regional water cycle [53]. This is achieved through high evapotranspiration, where forests transfer a significant amount of water to the atmosphere.…”
Section: ) Causal Links Between Vegetation and Meteorological Factors...mentioning
confidence: 67%
“…Further, forests change the Earth's surface albedo (Thompson et al 2009, Stephens et al 2015. Therefore, while forests in temperate and boreal regions generally warm the atmosphere during winter due to their low albedo, they predominantly cool it during the growing season, due to evapotranspiration (Chalita and Le Treut 1994, Ma et al 2017, Jiao et al 2021.…”
Section: General Introductionmentioning
confidence: 99%